Katjoe Manis Coffee In The Novel The Coffee Memory By Riawai Elyta: A Gastronomic Study - Sholikah, Ima Afiani; Indriyani, Jiphie Gilia (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2023)
This research aims to reveal the text that contains the aesthetic value of coffee in the novel The Coffee Memory by Riawani Elyta using Ronald Tobin’s gastronomic approach. The method used in this study is a qualitative analysis involving the resercher’s reading, recording, and interpretation of the text in the novel. The data collection technique involved carrying out reading and note-taking activities, which would then be analyzed by identifying and interpreting data and linking the data findings with gastronomic theory. This study obtained the results that the image of coffee can relate to the experiences experienced by humans. Not only that, but coffee also has aesthetic value, starting from its name, art, and the history of these unique coffees. Through that, culinary can have differences from other culinary delights, ultimately making it a person's identity.